Sustainability as a Function of an Area: Application of Multi-Criteria Evaluation in Assessing the Effectiveness of Nature-Based Solutions - Ewa Podhajska; Ewa Burszta-Adamiak; Anetta Drzeniecka-Osiadacz; Magdalena Zienowicz; Bronisław Podhajski; Tymoteusz Sawiński; Agnieszka Jasińska (Atmosphere, 2021)
One of the essential factors influencing the overall urban experience is the presence of biologically active surfaces. Despite widespread awareness of the beneficial effects of such spaces, the natural tissue in cities is still being significantly limited by the priority given to functionality and the economy. The aim of this article is to assess the potential of using a hybrid infrastructure in the grey–green–blue system (GGB) on a public site. In order to assess the efficiency of the implemented solutions, a multi-criteria method was developed, thereby recognising this research aspect as necessary in the process of designing urban built-up spaces. The assessment compared indicators of biological activity in the area using the biotope area factor and green space factor scales. The rainwater retention potential was estimated using a quantitative method. The change in the site’s thermal conditions was analysed by conducting numerous experiments with the use of micrometeorogical computational fluid dynamics models ENVI-met. The demonstrated improvement in the proportion of the biologically active area, water retention, and thermal conditions, ranging from a few to a dozen percent compared to the initial state, confirms the legitimacy of using grey–green–blue infrastructure systems as a method of shaping a sustainable and climate-responsive urban design.